O35-2 Current and cumulative night shift work and subclinical atherosclerosis – results of the gutenberg health study. (1st September 2016) - Jankowiak, Sylvia; Backé, Eva-Maria; Liebers, Falk; Schulz, Andreas; Hegewald, Janice; Garthus-Niegel, Susan; Nübling, Matthias; Blankenberg, Stefan; Pfeiffer, Norbert; Lackner, Karl J; Beutel, Manfred; Blettner, Maria; et al.
Abstract : Objectives: Research on shift work and cardiovascular health is challenging because of the long follow-up time that is needed to cover late outcomes such as myocardial morbidity (e.g., myocardial infarction), or mortality. The aim of this cross-sectional analysis was to investigate associations and dose-response relationships between (1) current and (2) cumulative exposure to night shift work and adverse effects on the surrogate parameters of atherosclerosis. Methods: Participants of a population-based cohort study (the Gutenberg Health Study, N = 15.010) aged 35–64 years were examined at baseline (2007 to 2012). Investigations included measurements of arterial stiffness, vascular function (reactive hyperemia [RH] index), and intima media thickness (IMT). Also, a complete job history (including up to 15 periods), occupational exposures, a variety of lifestyle and dispositional variables were enquired. Results: Night shift work was performed by 1, 071 out of 8, 065 currently employed individuals. The strongest association after adjustment for age, sex, job complexity level, being a manager, overtime work, and noise appeared for more than 660 night shifts within the last 10 years and a significantly increased arterial stiffness of 0.33 m/s. This reflects a 4 % flow velocity increase for individuals with more than 660 night shifts compared to non-night workers. Regarding the entire professional life, night shift workers showed a significantly decreased vascular function by −0.054 RH index points by using the same adjustment. IMT values did not differ statistically from non-night workers. Lifestyle and dispositional factors showed an influence on all used subclinical atherosclerosis parameters. Conclusions: The cross-sectional results demonstrate an association between night work and detrimental changes to the atherosclerotic process. The association is more pronounced with more years in night shift, and is partly explained by lifestyle and dispositional factors. Longitudinal analyses are necessary to confirm the results.